Wychowanie obywatelskie a problem nauczania historii – rekonstrukcja zachodniej debaty - Hejwosz-Gromkowska, Daria (Kultura-Społeczeństwo-Edukacja, 2013)
Some academics claim that history education is a vital component in citizenship education, others say that its role is overestimated. In the postmodern perspective there is “the end of the past” which is, to some extend, a product of consumption society and globalization. The contemporary societies are future-oriented and the rituals, myths and the need of belonging have nearly disappeared. In this context the questions about the purposes of history education and its relation to citizenship education are posed: should history education be nation-orientated to build loyalty and commitment or should it develop skills and knowledge for better comprehension of the present? Is history education oriented towards consensus or con ict? How to talk about history in multicultural societies, without marginalizing particular groups and without imperious imposition of the only version of “the Truth”? In order to answer to these question the reconstruction of the western debate has been made.